Lanthanum carbonate: safety data after 10 years. Issue 12 (December 2016) - Hutchison, Alastair J; Wilson, Rosamund J; Garafola, Svetlana; Copley, John Brian
Abstract: Despite 10 years of post‐marketing safety monitoring of the phosphate binder lanthanum carbonate, concerns about aluminium‐like accumulation and toxicity persist. Here, we present a concise overview of the safety profile of lanthanum carbonate and interim results from a 5‐year observational database study (SPD405‐404; ClinicalTrials.gov identifier: NCT00567723). The pharmacokinetic paradigms of lanthanum and aluminium are different in that lanthanum is minimally absorbed and eliminated via the hepatobiliary pathway, whereas aluminium shows appreciable absorption and is eliminated by the kidneys. Randomised prospective studies of paired bone biopsies revealed no evidence of accumulation or toxicity in patients treated with lanthanum carbonate. Patients treated with lanthanum carbonate for up to 6 years showed no clinically relevant changes in liver enzyme or bilirubin levels. Lanthanum does not cross the intact blood–brain barrier. The most common adverse effects are mild/moderate nausea, diarrhoea and flatulence. An interim Kaplan–Meier analysis of SPD405‐404 data from the United States Renal Data System revealed that the median 5‐year survival was 51.6 months (95% CI: 49.1, 54.2) in patients who received lanthanum carbonate (test group), 48.9 months (95% CI: 47.3, 50.5) in patients treated with other phosphate binders (concomitant therapy control group) and 40.3 months (95% CI: 38.9, 41.5) in patients before the availability of lanthanum carbonate (historical control group). Bone fracture rates were 5.9%, 6.7% and 6.4%, respectively. After more than 850 000 person‐years of worldwide patient exposure, there is no evidence that lanthanum carbonate is associated with adverse safety outcomes in patients with end‐stage renal disease. Summary at a Glance: Lanthanum carbonate is a non‐calcium‐based phosphate binder, and although it is a metal cation, its effects are not comparable with those of aluminium. This article discusses safety data of lanthanum with clinical studies showing no significant toxic effects after 10 years of follow‐up.